Relative importance of climate versus socio-environmental development changes to 2050 in rural coastal Bangladesh—a system analysis - Attila N. Lázár; Robert J. Nicholls; Craig W. Hutton; Andres Payo; Helen Adams; Anisul Haque; Derek Clarke; Mashfiqus Salehin; Alistair Hunt; Andrew Allan; W. Neil Adger; M. Munsur Rahman; et al. (Regional Environmental Change, 2026)
Climate change and development are having a profound influence on the integrity of coastal Bangladesh’s people, economy and ecology with climate change widely considered the dominant driver. Our bespoke integrated assessment model (IAM) simulates these changes for rural areas by coupling physical models with economic models, considering shocks like cyclone landfalls, and utilising substantial primary/secondary datasets and stakeholder-derived future scenarios. As such, this study assesses the Bangladesh coastal system’s sensitivity to climate change and policy decisions to 2050. The IAM results suggest that flooding and salinisation have high sensitivity to climatic and environmental drivers, and agricultural productivity is strongly dependent on farming methods and investment in better crop varieties to counteract these changes. Inequality, poverty and GDP per capita are more sensitive to non-climatic drivers. Nonetheless, extreme climatic conditions do impact livelihoods due to economic damage with variable effects across different household types. At least over the next 25 years, development choices (i.e. concrete adaptation actions) will have a similar if not stronger influence on livelihoods and economic wellbeing in rural coastal Bangladesh than climate-driven environmental change. This IAM approach supports decision makers to identify sustainable development pathways that address both current socio-environmental vulnerability as well as develop a more climate-resilient future.

Gone with the rain: capture, movement, and aestivation patterns of Siren intermedia - Jacob M. Hutton; Robin W. Warne (Wetlands Ecology and Management, 2025)

Allocating catches to species in mixed species data – A model-based approach - D. Parker; A.E. Punt; R.A. Deng; W.N. Venables; C.M. Dichmont; A.G. Donovan; R.A. Kenyon; T. van der Velde; M. Miller; T. Hutton (Fisheries Research, 2025)

Characterization of sites of scientific interest for ESA's PROSPECT instrument - S.J. Boazman; D. Heather; M. Hutton; M. Schwinning; A. Frigeri; N. Schmitz; S. Besse; M. Formisano; C. De Sanctis; C. Gscheidle; C. Orgel; P. Reiss; et al. (Icarus, 2024)

Where the rubber meets the road: Emerging environmental impacts of tire wear particles and their chemical cocktails - Paul M. Mayer; Kelly D. Moran; Ezra L. Miller; Susanne M. Brander; Stacey Harper; Manuel Garcia-Jaramillo; Victor Carrasco-Navarro; Kay T. Ho; Robert M. Burgess; Leah M. Thornton Hampton; Elise F. Granek; Margaret McCauley; et al. (Science of The Total Environment, 2024)

Inter- and intra-specific dietary overlap in predacious bi-phasic salamanders - Jacob M. Hutton; Stephen C. Richter; Steven J. Price (Hydrobiologia, 2023)

Integrating management of marine activities in Australia - Robert L. Stephenson; Alistair J. Hobday; Ian Butler; Toni Cannard; Mel Cowlishaw; Ian Cresswell; Christopher Cvitanovic; Jon C. Day; Kirstin Dobbs; Leo X.C. Dutra; Stewart Frusher; Maree Fudge; et al. (Ocean & Coastal Management, 2023)

Natural and synthetic microfibers alter growth and behavior in early life stages of estuarine organisms - S. Siddiqui; S. J. Hutton; J. M. Dickens; E. I. Pedersen; S. L. Harper; S. M. Brander (Frontiers in Marine Science, 2023)
Increasing shares of microfibers are being detected in environmental samples and a closer look to identify the risk associated with them using ecologically relevant endpoints, especially at sensitive early life stages, is needed. To assess exposure hazards, we used rope samples representative of fiber types ubiquitous in coastal systems, where microfibers are often the most common debris type found in the water column. To compare responses to natural vs. synthetic microfibers, we used rinsed “natural” cotton, polyester, and polypropylene microfibers (80-150 µm length, 8-20 µm width) created from the rope. Larval and juvenile estuarine indicator species Inland Silverside (Menidia beryllina) and mysid shrimp (Americamysis bahia) , respectively, were exposed to these three microfiber types at three concentrations (3, 10, 30 particles/ml) along a 5-25 PSU salinity gradient to mimic estuarine conditions. Behavioral responses, growth, and ingestion were measured. The cotton microfibers were not detected in the digestive tracts of Silversides, however, both the polyester and polypropylene microfibers were detected in the Silversides’ stomach and gut lining. None of the fiber types were detected in mysid shrimps. Mysids exposed to cotton microfibers had fewer behavioral effects compared to Silversides, who responded more to cotton. Cotton exerted no effect on growth in Silversides but did cause reduced growth in the mysids at the two lower salinities. In contrast, polyester and polypropylene were identified to have a significant dose dependent effect on mysid and Silverside behavior as well as growth was affected in at least one of the three salinities at concentrations as low as 3 particles/ml. Cotton impacted both the organism’s behavior more at higher salinities, whereas polyester and polypropylene had more impacts at lower salinities. This raises concerns for microfiber impacts on estuarine ecosystems and the need for policies to limit microfiber production and outfall into the aquatic environment.

Comparative behavioral ecotoxicology of Inland Silverside larvae exposed to pyrethroids across a salinity gradient - Sara J. Hutton; Samreen Siddiqui; Emily I. Pedersen; Christopher Y. Markgraf; Amelie Segarra; Michelle L. Hladik; Richard E. Connon; Susanne M. Brander (Science of The Total Environment, 2023)

Prediction of enteric methane emissions by sheep using an intercontinental database - Alejandro Belanche; Alexander N. Hristov; Henk J. van Lingen; Stuart E. Denman; Ermias Kebreab; Angela Schwarm; Michael Kreuzer; Mutian Niu; Maguy Eugène; Vincent Niderkorn; Cécile Martin; Harry Archimède; et al. (Journal of Cleaner Production, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Contrasting Futures for Australia’s Fisheries Stocks Under IPCC RCP8.5 Emissions – A Multi-Ecosystem Model Approach - Heidi R. Pethybridge; Elizabeth A. Fulton; Alistair J. Hobday; Julia Blanchard; Catherine M. Bulman; Ian R. Butler; William W. L. Cheung; Leo X. C. Dutra; Rebecca Gorton; Trevor Hutton; Richard Matear; Hector Lozano-Montes; et al. (Frontiers in Marine Science, 2020)

From the Lab to Patients: a Systematic Review and Meta-Analysis of Mesenchymal Stem Cell Therapy for Stroke - Manoj M. Lalu; Joshua Montroy; Dar Dowlatshahi; Brian Hutton; Pascale Juneau; Neil Wesch; Sarah Y. Zhang; Ryan McGinn; Dale Corbett; Duncan J. Stewart; Dean A. Fergusson (Translational Stroke Research, 2020)

Collective influence of household and community capitals on agricultural employment as a measure of rural poverty in the Mahanadi Delta, India - Tristan Berchoux; Gary R. Watmough; Fiifi Amoako Johnson; Craig W. Hutton; Peter M. Atkinson (Ambio, 2020)

Ty-6, a major begomovirus resistance gene on chromosome 10, is effective against Tomato yellow leaf curl virus and Tomato mottle virus - Upinder Gill; John W. Scott; Reza Shekasteband; Eben Ogundiwin; Cees Schuit; David M. Francis; Sung-Chur Sim; Hugh Smith; Samuel F. Hutton (Theoretical and Applied Genetics, 2019)

Trace element concentrations in feathers of seven petrels (Pterodroma spp.) - Susan M. Philpot; Jennifer L. Lavers; Dayanthi Nugegoda; Morgan E. Gilmour; Ian Hutton; Alexander L. Bond (Environmental Science and Pollution Research, 2019)

Wrestling with the complexity of evaluation for organizations at the boundary of science, policy, and practice - R. Pitt; C. Wyborn; G. Page; J. Hutton; M. Virah Sawmy; M. Ryan; L. Gallagher (Conservation Biology, 2018)
Boundary organizations are situated between science, policy, and practice and have a goal of supporting communication and collaboration among these sectors. They have been promoted as a way to improve the effectiveness of conservation efforts by building stronger relationships between scientists, policy makers, industry, and practitioners (Cook et al. 2013). Although their promise has been discussed in theory, the work of and expectations for boundary organizations are less defined in practice. Biodiversity conservation is characterized by complexity, uncertainty, dissent, and tight budgets, so boundary organizations face the challenging task of demonstrating their value to diverse stakeholders. We examined the challenges boundary organizations face when seeking to evaluate their work and thus aimed to encourage more productive conversations about evaluation of boundary organizations and their projects. Although no off‐the‐shelf solution is available for a given boundary organization, we identified 4 principles that will support effective evaluation for boundary organizations: engage diverse stakeholders, support learning and reflection, assess contribution to change, and align evaluation with assumption and values.

NiftyPET: a High-throughput Software Platform for High Quantitative Accuracy and Precision PET Imaging and Analysis - Pawel J. Markiewicz; Matthias J. Ehrhardt; Kjell Erlandsson; Philip J. Noonan; Anna Barnes; Jonathan M. Schott; David Atkinson; Simon R. Arridge; Brian F. Hutton; Sebastien Ourselin (Neuroinformatics, 2018)

Integrated ecological–economic fisheries models—Evaluation, review and challenges for implementation - J Rasmus Nielsen; Eric Thunberg; Daniel S Holland; Jorn O Schmidt; Elizabeth A Fulton; Francois Bastardie; Andre E Punt; Icarus Allen; Heleen Bartelings; Michel Bertignac; Eckhard Bethke; Sieme Bossier; et al. (Fish and Fisheries, 2018)
Marine ecosystems evolve under many interconnected and area‐specific pressures. To fulfil society's intensifying and diversifying needs while ensuring ecologically sustainable development, more effective marine spatial planning and broader‐scope management of marine resources is necessary. Integrated ecological–economic fisheries models ( IEEFM s) of marine systems are needed to evaluate impacts and sustainability of potential management actions and understand, and anticipate ecological, economic and social dynamics at a range of scales from local to national and regional. To make these models most effective, it is important to determine how model characteristics and methods of communicating results influence the model implementation, the nature of the advice that can be provided and the impact on decisions taken by managers. This article presents a global review and comparative evaluation of 35 IEEFM s applied to marine fisheries and marine ecosystem resources to identify the characteristics that determine their usefulness, effectiveness and implementation. The focus is on fully integrated models that allow for feedbacks between ecological and human processes although not all the models reviewed achieve that. Modellers must invest more time to make models user friendly and to participate in management fora where models and model results can be explained and discussed. Such involvement is beneficial to all parties, leading to improvement of mo‐dels and more effective implementation of advice, but demands substantial resources which must be built into the governance process. It takes time to develop effective processes for using IEEFM s requiring a long‐term commitment to integrating multidisciplinary modelling advice into management decision‐making.

Estrogen, progesterone, and HER2/neu receptor discordance between primary and metastatic breast tumours—a review - C. Yeung; J. Hilton; M. Clemons; S. Mazzarello; B. Hutton; F. Haggar; C. L. Addison; I. Kuchuk; X. Zhu; K. Gelmon; A. Arnaout (Cancer and Metastasis Reviews, 2016)

Multispecies fisheries management and conservation: tactical applications using models of intermediate complexity - Éva E Plagányi; André E Punt; Richard Hillary; Elisabetta B Morello; Olivier Thébaud; Trevor Hutton; Richard D Pillans; James T Thorson; Elizabeth A Fulton; Anthony D M Smith; Franz Smith; Peter Bayliss; et al. (Fish and Fisheries, 2014)
Stakeholders increasingly expect ecosystem assessments as part of advice on fisheries management. Quantitative models to support fisheries decision‐making may be either strategic (‘big picture’, direction‐setting and contextual) or tactical (focused on management actions on short timescales), with some strategic models informing the development of tactical models. We describe and review ‘ M odels of I ntermediate C omplexity for E cosystem assessments’ ( MICE ) that have a tactical focus, including use as ecosystem assessment tools. MICE are context‐ and question‐driven and limit complexity by restricting the focus to those components of the ecosystem needed to address the main effects of the management question under consideration. Stakeholder participation and dialogue is an integral part of this process. MICE estimate parameters through fitting to data, use statistical diagnostic tools to evaluate model performance and account for a broad range of uncertainties. These models therefore address many of the impediments to greater use of ecosystem models in strategic and particularly tactical decision‐making for marine resource management and conservation. MICE are capable of producing outputs that could be used for tactical decision‐making, but our summary of existing models suggests this has not occurred in any meaningful way to date. We use a model of the pelagic ecosystem in the C oral S ea and a linked catchment and ocean model of the G ulf of C arpentaria, A ustralia, to illustrate how MICE can be constructed. We summarize the major advantages of the approach, indicate opportunities for the development of further applications and identify the major challenges to broad adoption of the approach.

Mineral system analysis of the Mt Isa–McArthur River region, Northern Australia - F. C. Murphy; L. J. Hutton; J. L. Walshe; J. S. Cleverley; M. A. Kendrick; J. Mclellan; M. J. Rubenach; N.H. S. Oliver; K. Gessner; F. P. Bierlein; B. Jupp; L. Aillères; et al. (Australian Journal of Earth Sciences, 2011)

Oil and gas development in the World Heritage and wider protected area network in sub-Saharan Africa - Matea Osti; Lauren Coad; Joshua B. Fisher; Bastian Bomhard; Jonathan M. Hutton (Biodiversity and Conservation, 2011)

Identification of QTL associated with resistance to bacterial spot race T4 in tomato - Samuel F. Hutton; Jay W. Scott; Wencai Yang; Sung-Chur Sim; David M. Francis; Jeffrey B. Jones (Theoretical and Applied Genetics, 2010)

One Hundred Questions of Importance to the Conservation of Global Biological Diversity - W. J. SUTHERLAND; W. M. ADAMS; R. B. ARONSON; R. AVELING; T. M. BLACKBURN; S. BROAD; G. CEBALLOS; I. M. CÔTÉ; R. M. COWLING; G. A. B. DA FONSECA; E. DINERSTEIN; P. J. FERRARO; et al. (Conservation Biology, 2009)
We identified 100 scientific questions that, if answered, would have the greatest impact on conservation practice and policy. Representatives from 21 international organizations, regional sections and working groups of the Society for Conservation Biology, and 12 academics, from all continents except Antarctica, compiled 2291 questions of relevance to conservation of biological diversity worldwide. The questions were gathered from 761 individuals through workshops, email requests, and discussions. Voting by email to short‐list questions, followed by a 2‐day workshop, was used to derive the final list of 100 questions. Most of the final questions were derived through a process of modification and combination as the workshop progressed. The questions are divided into 12 sections: ecosystem functions and services, climate change, technological change, protected areas, ecosystem management and restoration, terrestrial ecosystems, marine ecosystems, freshwater ecosystems, species management, organizational systems and processes, societal context and change, and impacts of conservation interventions. We anticipate that these questions will help identify new directions for researchers and assist funders in directing funds.

Non-cholinergic modulation of antisaccade performance: a modafinil-nicotine comparison - N. Rycroft; S. B. Hutton; O. Clowry; C. Groomsbridge; A. Sierakowski; J. M. Rusted (Psychopharmacology, 2007)

The antisaccade task as an index of sustained goal activation in working memory: modulation by nicotine - Nicola Rycroft; Samuel B. Hutton; Jennifer M. Rusted (Psychopharmacology, 2006)

Acute effects of nicotine on visual search tasks in young adult smokers - Nicola Rycroft; Jennifer M. Rusted; Samuel B. Hutton (Psychopharmacology, 2005)

Plant hosts of the phytoplasmas and rickettsia-like-organisms associated with strawberry lethal yellows and green petal diseases - Claire Streten; Mark E. Herrington; Don G. Hutton; Denis M. Persley; Geoff K. Waite; Karen S. Gibb (Australasian Plant Pathology, 2005)

Rickettsia-like-organisms and phytoplasmas associated with diseases in Australian strawberries - Claire Streten; Geoff K. Waite; Mark E. Herrington; Don G. Hutton; Denis M. Persley; Karen S. Gibb (Australasian Plant Pathology, 2005)

Modeling Continental Shelf Formation in the Adriatic Sea and Elsewhere - Lincoln Pratson; John Swenson; Albert Kettner; Juan Fedele; George Postma; Alan Niedoroda; Carl Friedrichs; James Syvitski; Chris Paola; Mike Steckler; Eric Hutton; Christopher Reed; et al. (Oceanography, 2004)

Failure of Marine Deposits and their Redistribution by Sediment Gravity Flows - J. P. M. Syvitski; E. W. H. Hutton (Pure and Applied Geophysics, 2003)

Turbulence Statistics Measurements in a Northern Hardwood Forest - M. G. Villani; H. P. Schmid; H.-B. Su; J. L. Hutton; C. S. Vogel (Boundary-Layer Meteorology, 2003)

Building the infrastructure for nationwide cancer surveillance and control – a comparison between The National Program of Cancer Registries (NPCR) and The Surveillance, Epidemiology, and End Results (SEER) Program (United States) - Phyllis A. Wingo; Patricia M. Jamison; Robert A. Hiatt; Hannah K. Weir; Paul M. Gargiullo; Mary Hutton; Nancy C. Lee; H. Irene Hall (Cancer Causes & Control, 2003)

Accumulation and renal effects of lead in urban populations of feral pigeons,Columba livia - M. S. Johnson; H. Pluck; M. Hutton; G. Moore (Archives of Environmental Contamination and Toxicology, 1982)